ANALISIS BAHAYA GEMPA BUMI LENGAN UTARA SULAWESI - Santoso Santoso; Asdani Soehaimi (Pusat Survei Geologi, 2010)
The Megatrust and Benioff subduction seismic sources of the Sulawesi Sea Micro Plate subducted at 100 km beneath of North Sulawesi's Arm have significant effect in radius of 150 km in this peninsula. The Deterministic Seismic Hazard Analysis-DSHA from megathrust seismic source zone using attenuation function model of Young et al (1997) to the Manado City result in 0.22 g, equal to VIII MMI. Microzonation efforts in this region are conducted in order to mitigate future seismic hazards.Keyword: Seismic hazard, attennation function, Maximum Credible Earthquake (MCE) and Maximum intensity